Expression and clinical significance of HSP27 and its phosphorylation in lower extremity arteriosclerosis obliterans - Bai, Junqing; Wang, Fule; Wang, Xuguang; Mutu, Eerde; Duan, Chen; Qi, Yili; Hu, Liqiang; Gao, Zhanfeng (PeerJ, 2020)
Objectives This study set out to analyze the difference of heat shock protein 27 (HSP27) and its phosphorylation in patients with lower extremity arteriosclerosis obliterans (LEASO) at different stages. This research also examined their clinical significance in this disease. Methods Blood samples from 60 patients with LEASO were collected and divided into two groups according to ankle-brachial index (ABI): group A (ABI ≤ 0.43) and group B (ABI > 0.43). The expression of HSP27 in each stage of Fontaine was measured by ELISA, and the difference of HSP27 concentration and ABI between the two groups was analyzed. Meanwhile, three normal femoral artery specimens (normal group) and three atherosclerotic femoral artery specimens (lesion group) were collected, and HSP27 and its Phospho-HSP27 (Ser15), Phospho-HSP27 (Ser78) and Phospho-HSP27 (Ser82) were detected by western blotting. The data of the protein level between the normal group and the lesion group was made a statistical analysis. Results HSP27 concentration in group A was (40.73 ± 15.99) ng/ml, and ABI was 0.26 ± 0.20. HSP27 concentration in group B was (66.30 ± 24.70) ng/ml, and ABI was 0.64 ± 0.20. The protein expression of HSP27 and its phosphorylation in the normal group was 0.82 ± 0.13, 0.66 ± 0.12, 0.91 ± 0.24 and 0.90 ± 0.16, respectively; the protein expression of the lesion group was 0.45 ± 0.08, 0.42 ± 0.09, 0.39 ± 0.12 and 0.58 ± 0.11. Conclusion Patients with higher LEASO Fontaine stage and lower ABI had a lower HSP27 concentration. Serum HSP27 concentration was negatively correlated with the severity of LEASO, while HSP27 concentration was positively correlated with ABI value. The content of HSP27 and its phosphorylation of lesion group is significantly lower than that of normal group, which may be closely related to the occurrence and development of atherosclerosis.
Keywords: Lower extremity arteriosclerosis obliterans; Heat shock protein 27